Modelagem estocástica de estruturas compósitas incorporando circuitos Shunt para o controle passivo de vibrações - Ribeiro, Lorrane Pereira (2015)
Engineering composite structures containing piezoelectric elements coupled with the so-named shunt circuits, with the aim of passive vibration attenuation, are characterized by inherent uncertainties in their parameters, which can affect significantly performance of the passive shunt circuit. In this context, this work presents the stochastic finite element modeling of a composite structure containing piezoelectric element to be coupled with a shunt circuit, in such a way, that uncertain parameters such as the fiber s orientation, layer thicknesses and the resistance and inductance in the shunt circuit are assumed as uncertain variables and, their corresponding dispersion, is characterized in the stochastic response by propagating the uncertainties into the model. First, the deterministic electromechanical problem is modeled by combining the First-Order Shear Deformation Theory and the concept of Equivalent Single Layer, in order to approximate the mechanical displacement fields, with the so-called Layerwise Theory used to model the discrete electric fields within the composite element. In the sequence, the shunt circuits coupled to the piezoelectric element are introduced in the model. The deterministic finite element modeling procedure was performed taking into the parameterization process of the design variables of interest to be further assumed as random variables in a straightforward way. In the present stochastic finite element modeling procedure, the uncertain variables are modeled as Gaussian stochastic homogeneous fields and discretized according to the Karhunen-Loève expansion method, with the aim of generating the exact stochastic matrices. The obtained results, in terms of the envelopes of the frequency response functions for a composite beam incorporating piezoelectric material coupled with a shunt circuit, demonstrate the interest in considering the uncertainties in the preliminary design phase of the shunt circuits to control the undesired vibrations.